2010
DOI: 10.1021/ja102040u
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Nanospheres with Bicontinuous Internal Structures from a Semicrystalline Amphiphilic Block Copolymer

Abstract: Internally structured self-assembled nanospheres, cubosomes, are formed from a semi-crystalline block copolymer, poly(ethylene oxide)-block-poly(octadecyl methacrylate) (PEO39-b-PODMA17), in aqueous dispersion. The poly(octadecyl methacrylate) block provides them with a temperature responsive structure and morphology. Using cryo-electron tomography, we show that at room temperature these internally bicontinuous aggregates undergo an unprecedented order-disorder transition of the microphase separated domains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 43 publications
11
109
0
Order By: Relevance
“…These were dissolved in an alkane solvent (e.g., hexane) which lead to the formation of rod-like micelles, driven by the formation of a hexane insoluble PFS core and a hexane swollen PI or PDMS corona. While the majority of block copolymer based morphologies described in the literature are formed under conditions close to thermodynamic control and subsequently trapped in kinetically frozen states, [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Winnik and Manners were able to exploit the crystalline nature of PFS in order to manipulate the growth into one-dimensional micelles of controlled length and architecture. 31 By heating the hexane solution of block copolymers to 60 8C, free unimer chains were obtained that upon slow cooling produce a discrete number of nuclei, a process described as the nucleation phase.…”
Section: Living Supramolecular Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These were dissolved in an alkane solvent (e.g., hexane) which lead to the formation of rod-like micelles, driven by the formation of a hexane insoluble PFS core and a hexane swollen PI or PDMS corona. While the majority of block copolymer based morphologies described in the literature are formed under conditions close to thermodynamic control and subsequently trapped in kinetically frozen states, [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Winnik and Manners were able to exploit the crystalline nature of PFS in order to manipulate the growth into one-dimensional micelles of controlled length and architecture. 31 By heating the hexane solution of block copolymers to 60 8C, free unimer chains were obtained that upon slow cooling produce a discrete number of nuclei, a process described as the nucleation phase.…”
Section: Living Supramolecular Polymerizationmentioning
confidence: 99%
“…Strategies to control the size and shape of nano-and micrometer size objects that rely on selective solvent techniques in the self-assembly of block copolymers will not be discussed here. [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Supramolecular multicomponent gels, [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] or orthogonal self-assembly, [90][91][92][93][94][95][96][97] self-sorting [98][99][100][101][102][103][104] and chiral amplification strategies 105 in multicomponent supramolecular polymers will not be covered in detail, and the interested reader is referred to the recent literature and review articles.…”
mentioning
confidence: 99%
“…Similarly one can envision the use of the selfassembled bicontinous block polymer templates for controlled formation of complex mineral morphologies. Such complex block copolymer micelles with a bicontinuous interior were recently demonstrated for a poly-octadecyl methacrylate (PODMA)-based block copolymer [53]. Mineralization of their interior and subsequent chemical conversion of the hydrophobic (PODMA) blocks to hydrophilic PAA blocks would provide the space and the templating capability required for the deposition of a second mineral phase inside the first one.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 We have previously reported on the thermo-responsive nature of bicontinuous polymer nanospheres (BPNs) that selfassembled in aqueous dispersions from PEO-b-PODMA. 6 BPNs are discrete aggregates that have a twisted hydrophobic network interconnected with that of a hydrophobic moiety. The self-assembly of BPNs from PEO-b-PODMA has been investigated previously by Holder and Sommerdijk et al and it was found that the weight fraction of the hydrophilic block (PEO) should be between 15-25% with the molecular weight at < 17 kDa for BPNs to form.…”
Section: Introductionmentioning
confidence: 99%